Overview of the Node.js ecosystem : when to use Node.js in your development projects - Higbee, Wes (O'Reilly, 2016)
"In this Overview of the Node.js Ecosystem training course, expert author Wes Higbee teaches you when to use Node.js in your development projects. This course is designed for users that are familiar with HTML, CSS, and JavaScript. You will start by learning about the history of Node.js and why you should use Node.js. From there, Wes will teach you about architecture, including simplified currency and callback convention. This video tutorial also covers modularity, such as modules in Node.js, CommonJS, and Node.js core modules. Finally, you will learn about npm, including package management, using an npm package, and popular packages. Once you have completed this computer based training course, you will have learned when to use Node.js in your development projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.